The effect of work environment, compensation, career development, leadership, and workload on job satisfaction with work motivation as an intervening variable - Nugroho, Sukmo Hadi; Said, Meldasari; Said, Laila Refiana (Annals of Human Resource Management Research, 2025)
Purpose: This study aimed to analyze the influence of work environment, compensation, career development, leadership, and workload (as independent variables) on employee job satisfaction (as the dependent variable) in the healthcare sector, particularly in hospitals. Additionally, this study aimed to test the significant influence of work motivation (as an intervening variable) on the relationship between these variables. Research Methodology: The research method used was a quantitative method with an explanatory research approach, utilizing Structural Equation Modeling (SEM) and SMART-PLS. Results: The results of this study indicate that all independent variables show a significant positive relationship with the dependent variable, except for the workload variable, which shows a significant negative relationship. The influence of the relationships between variables is expressed in terms of Effect Size. The variables most directly influencing Work Motivation are Compensation with an Effect Size of 0.787, and Career Advancement with an Effect Size of 0.769. Work Motivation, as an intervening variable, was also found to significantly influence the relationship between the independent variables (Work Environment, Compensation, Career Advancement, Leadership, Workload) and the dependent variable (Job Satisfaction). Conclusions: The study found that all independent variables significantly affected job satisfaction both directly and indirectly through work motivation, with compensation and career advancement having the strongest effects, while excessive workload negatively impacted motivation and satisfaction. Limitations: This study was limited to a single private hospital in Jakarta, which may affect the generalizability of the findings to other healthcare institutions or regions. Contribution: This study provides useful recommendations for hospital management to enhance employee motivation and job satisfaction.